Comparative Analytical Study of Tax Legislation and its Impact on foreign Direct Investment - AlDahabi, Zain Mohammed; Algazo, Fatima Ali; Alanazi, Amal Marshed; Hajjaj, Rula Yousef (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to investigate the relationship between tax policies and foreign direct investment (FDI) attraction, focusing on the impact of tax rates, incentives, tax exemptions, and the stability of the legal framework on investors' decisions. The research methodology is based on a comparative analysis combining quantitative and qualitative data from reports and assessments from prestigious international institutions such as the World Bank, the International Monetary Fund (IMF), and the Organization for Economic Co-operation and Development (OECD). The study divides countries into three groups: the first group includes countries with tax-friendly policies, such as Singapore and the UAE; the second group comprises countries with significant legislative stability, such as Germany and Canada; and the third group includes countries that face frequent legislative fluctuations, often found in developing countries. The results indicate that transparency and the stability of the tax system are crucial factors in enhancing investor confidence and increasing capital inflows. Conversely, high tax rates and frequent legislative changes contribute to reducing the attractiveness of the investment environment, making investors more hesitant in their decision-making. The study also highlights the positive impact of double taxation avoidance agreements in alleviating the financial burdens on foreign companies, which further enhances investment attraction. Ultimately, the study recommends adopting stable tax policies and conditional incentives to foster and sustain foreign direct investments.
Keywords: Tax Legislation; Foreign Direct Investment; Investment Incentives; Legislative Stability; Tax Agreements